The Validation of the Helicobacter pylori CagA Typing by Immunohistochemistry: Nationwide Application in Indonesia - Miftahussurur, Muhammad (Acta Histochem, 2020)
We aimed to validate 2 types of antibodies, anti-CagA antibody and anti-East Asian CagA specific antibody (α-EAS antibody) for the determination of CagA status in Indonesia. We also confirmed the performance of α-EAS antibody for the detection of East Asian-type CagA H. pylori. Immunohistochemistry was performed using anti-CagA antibody and α-EAS antibody on gastric biopsy specimens from a total of 967 Indonesian patients. Diagnostic values of immunohistochemistry were evaluated with PCR-based sequencing as gold standard. Anti-CagA antibody had high sensitivity, specificity, and accuracy (87.0%, 100%, and 98.8%, respectively) for determining CagA status. The α-EAS antibody was not suitable for the purpose of CagA status determination, as it had a low sensitivity (23.9%). High specificity (97.6%) but low sensitivity (41.2%) and accuracy (66.3%) was observed in α-EAS antibody to detect East Asian-type CagA. Patients with positive result of immunohistochemistry using anti-CagA antibody had significantly higher monocyte infiltration score in antrum (P < 0.001) and corpus (P = 0.009). In conclusion, the anti-CagA antibody is still suitable to be used in Indonesia for determining the CagA status, whilst the α-EAS antibody was not appropriate to discriminate between East Asian-type and non-East Asian-type CagA in Indonesia.